Effect of Sambucus nigra inflorescence supplementation on the organism of rats fed a high-fat diet - Lieshchova, M. A.; Brygadyrenko, V. V. (Regulatory Mechanisms in Biosystems, 2024)
Medicinal plants are interesting as mild and effective therapeutic agents for treating and correcting metabolic disorders caused by an unbalanced diet. Sambucus nigra has antioxidant and anti-inflammatory properties, which are used to alleviate cardiovascular, neurodegenerative and inflammatory diseases. It also has antidiabetic, anticancer, antiviral and immunostimulant properties. The effect of adding crushed S. nigra inflorescences to the diet of rats was modelled under experimental laboratory conditions. For this purpose, three groups of 5 animals each were formed from white male laboratory rats that were fed a high-fat diet (15% vegetable fat) for 35 days, with the addition of 0.5% and 2.0% dry crushed S. nigra inflorescences. The overall effect of introducing the plant in the high-fat diet on body weight gain, the relative weight of some internal organs and the state of metabolic processes in the model animals was assessed. In the high-fat diet group, body weight increased to 108% of baseline at the end of the experiment. Supplementing the diet with S. nigra inflorescences at a dose of 0.5% promoted an increase in body weight gain (up to 112% of the initial weight), and a dose of 2.0% caused a slowdown and even a decrease in body weight at the end of the experiment. A high-fat diet supplemented with 2.0% of S. nigra inflorescences significantly increased the relative weights of liver, lung and spleen, whereas 0.5% of the plant did not cause significant changes in these indices. The addition of 2.0% of S. nigra inflorescences to the diet of animals significantly reduced blood glucose concentration. Both doses reduced the level of low-density lipoprotein (LDL) cholesterol in the blood, and the 2.0% dose also increased the level of high-density lipoprotein (HDL) cholesterol, while the amount of total cholesterol in the blood did not change and the atherogenicity index decreased. The addition of S. nigra inflorescences to the high-fat diet did not cause changes in protein and mineral metabolism, but did affect bilirubin metabolism, especially the levels of direct and indirect bilirubin. Both doses of elderflower caused a significant decrease in alpha-amylase activity, ALT activity and a strong significant increase in the De Ritis ratio. The results show the possibility of using dried S. nigra inflorescences as a dietary supplement in unbalanced diets to correct possible metabolic disorders.